Calibration and Optimization of p53, WT1, and Napsin A Immunohistochemistry Ancillary Tests for Histotyping of Ovarian Carcinoma: Canadian Immunohistochemistry Quality Control (CIQC) Experience. (May 2016) - Lee, Sandra; Piskorz, Anna M.; Le Page, Cécile; Mes Masson, Anne-Marie; Provencher, Diane; Huntsman, David; Chen, Wenqian; Swanson, Paul E.; Gilks, C. Blake; Köbel, Martin
Abstract : The Canadian Immunohistochemistry Quality Control provides proficiency testing for immunohistochemistry in Canadian laboratories. Canadian Immunohistochemistry Quality Control Run 42 assessed WT1, Napsin A, and p53; commonly used markers for histotyping ovarian carcinomas. A 42-core tissue microarray, which included the 5 major histotypes of ovarian carcinomas with a subset having known TP53 mutational status, was used for this Canadian Immunohistochemistry Quality Control challenge. Participants included 43 laboratories for p53, 29 for WT1, and 26 for Napsin A. p53 was scored as aberrant if the staining was strong and diffuse or absent. Napsin A and WT1 were scored positive if any tumor cells stained. The reference p53 expression pattern was inferred by TP53 mutation type when available. For WT1, Napsin A, and cases lacking mutational data, the reference staining pattern was based on the majority staining result. The error rate for p53 was 8.8%. Most errors (84%) were due to weak staining. The sensitivity and specificity of aberrant p53 expression for an underlying TP53 mutation was 91.6% and 87.9%, respectively. The error rate for WT1 was 0.76% with all errors occurring in laboratories using the 6F-h2 clone. The average errors for laboratories using 6F-h2 were 2.4 compared with 0 for WT-49. The error rate for Napsin A was 4%. The average errors for laboratories using polyclonal Napsin A were 3 compared with 1.1 for monoclonal Napsin A. Weak p53 staining increases interpretative errors, primarily due to absence of staining in tumors with wild-type TP53 . p53 immunohistochemistry correlates strongly with TP53 mutational status. Polyclonal Napsin A and 6F-h2 may lack specificity in comparison to monoclonal Napsin A and WT-49.